Unemployment Benefits and Labor Market Transitions: A Multinomial Logit Model with Errors in Classification - Poterba, James M.; Summers, Lawrence H. (The Review of Economics and Statistics, 1995)
James M. Poterba, Lawrence H. Summers, Unemployment Benefits and Labor Market Transitions: A Multinomial Logit Model with Errors in Classification, The Review of Economics and Statistics, Vol. 77, No. 2 (May, 1995), pp. 207-216